Early-stage outcomes and cost-effectiveness of implementing tourism-led coral propagation and outplanting in the Whitsundays (Great Barrier Reef) - Scott, Rachael; Suggett, David; Hayward, Cassidy; Chatterton, Brent; Edmondson, John; Gaskell, Johnny; Gillette, Gemma M.; Howlett, Lorna; Monacella, Emily; Roper, Christine D.; Strudwick, Paige; Unsworth, James; et al. (Frontiers in Marine Science, 2024)
Implementation of coral restoration practices within reef management strategies is accelerating globally to support reef resilience and recovery. However, full costs underpinning restoration project feasibility have historically been underreported yet are critical to informing restoration cost-benefit decision-making. Such knowledge is especially lacking for Australia’s Great Barrier Reef (GBR), where a coral restoration program led by reef tourism operators, Coral Nurture Program (CNP), was initiated in 2018 (northern GBR) and continues to scale. Here we describe the early outcomes and costs of implementing similar tourism-led asexual coral propagation and outplanting practices in a new region, the Whitsundays (central GBR) through the CNP. Specifically, we detail the local operational and environmental context of CNP Whitsundays, describe the costs of implementation and continuation of restoration activities, as well as evaluate survivorship of coral outplants across three restoration sites for nine months after project establishment (August 2022 to June 2023). Baseline benthic surveys revealed relatively low hard coral cover at restoration sites (ranging from 3.22-8.67%), which significantly differed in benthic composition from coral collection sites (ranging 16.67-38.06%), supporting strong motivation by tourism operators to undertake restoration activities. Mean coral survivorship of coral outplants in fate-tracked plots differed between the three restoration sites after 267 days (ranging 23.33-47.58%), with declines largely driven by coral detachment. Early-stage cost-effectiveness (costs relative to outplant survival) associated with implementation of restoration activity varied widely from US33.04-178.55 per surviving coral (n = 4,425 outplants) depending on whether ‘in-kind’ costs, restoration activity (outplanting only vs. total costs encompassing planning through to monitoring), site-based survivorship, or a combination of these factors, were considered. As coral reef restoration projects continue to be established globally, our results highlight the need for ongoing, long-term monitoring that can inform adaptive practice, and fully transparent cost-reporting to understand and improve feasibility for any given project. We further highlight the inherent context-dependency of restoration costs, and the importance of considering local social-environmental contexts and their associated cost-benefits in economic rationale for reef restoration projects.